Respuesta :

The answer is B. y = -cos(x)

Answer:

The function that is shown in the graph is:

y= -cos x

Step-by-step explanation:

We are given a graph of a function we have to recognize which function is represented by the given graph.

Clearly we could observe from the graph that the function takes the value -1 at x=0.

Hence, the function which satisfy this condition is:

                  y= -cos x

( since at x=0

y= -cos 0=-1

Also at x=π

we get

y= -cos(π)=-(-1)=1

similarly at x= -π

we get:

y= -cos(-π)= -(-1)=1)

ACCESS MORE